Lessons from investigation of regulation of APS reductase by salt stress - Koprivova, Anna (Landes Bioscience, 2008)
Exposure to high salinity affects plant ion homeostasis, water relations and results in oxidative stress. Therefore, various processes are induced as salt stress response including antioxidative defense systems. The tripeptide glutathione has a prominent position among the metabolites involved in such stress defense. Glutathione synthesis is dependent on supply of cysteine and thus on the assimilation of sulfate. We have investigated how the key enzyme of sulfate assimilation, adenosine 5′phosphosulfate (APS) reductase is regulated by salt stress in Arabidopsis roots. Using Arabidopsis mutants in various signaling pathways we aimed to identify the signaling cascade leading to regulation of APS reductase by NaCl. We found the enzyme to be regulated by a complex signaling network on transcriptional and post-transcriptional levels with responses of mRNA accumulation and enzyme activity largely uncoupled. Here we want to share the important lessons we have learned from this investigations.